2013
DOI: 10.1039/c3dt32550d
|View full text |Cite
|
Sign up to set email alerts
|

Morphology controlled NH4V3O8 microcrystals by hydrothermal synthesis

Abstract: Single crystalline ammonium trivanadate NH4V3O8 with variable morphologies, including shuttles, flowers, belts, and plates, was synthesized by the hydrothermal treatment of NH4VO3 with acetic acid. The crystals optimally grow under gentle conditions of 140 °C for 48 h. The resulting NH4V3O8 microcrystals were characterized by means of X-ray diffraction, scanning electron microscopy, infrared and Raman spectroscopy, static magnetization studies, and thermal analysis. The key factors to control the size and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…Thus, it can be concluded that the chemically cleaned Bi 2 Te 3 (0001) surface can be prepared by the crystal cleavage in the air environment. The specially exposed facets of crystals have been demonstrated to show enhanced properties in various applications [74][75][76][77][78][79][80][81][82]. The Bi 2 Se 3 -type crystals, including Bi 2 Te 3 , possess strongly specific properties of the (0001) surface and this factor should be accounted in the microcrystal growth and TI structure preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the chemically cleaned Bi 2 Te 3 (0001) surface can be prepared by the crystal cleavage in the air environment. The specially exposed facets of crystals have been demonstrated to show enhanced properties in various applications [74][75][76][77][78][79][80][81][82]. The Bi 2 Se 3 -type crystals, including Bi 2 Te 3 , possess strongly specific properties of the (0001) surface and this factor should be accounted in the microcrystal growth and TI structure preparation.…”
Section: Resultsmentioning
confidence: 99%
“…. The stretching vibration in the range of 3700-2900 cm -1 probably results from the presence of a dense network of hydrogen bonds [18]. The chemical composition and valence state of the product were further studied by XPS.…”
Section: Resultsmentioning
confidence: 99%
“…2b) and the resulting crystals are in the shape of 2D nanosheets (Fig. 1a) [18]. At a pH of 3.0, the vanadium precursor exists as octahedral [VO(OH) 3 (H 2 O) 2 ] 0 (Fig.…”
Section: Morphology Tuning By Reaction Phmentioning
confidence: 99%